2022
DOI: 10.1186/s13195-022-00959-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel D-amino acid peptide with therapeutic potential (ISAD1) inhibits aggregation of neurotoxic disease-relevant mutant Tau and prevents Tau toxicity in vitro

Abstract: Background Alzheimer’s disease (AD), the most common form of dementia, is a progressive neurodegenerative disorder that mainly affects older adults. One of the pathological hallmarks of AD is abnormally aggregated Tau protein that forms fibrillar deposits in the brain. In AD, Tau pathology correlates strongly with clinical symptoms, cognitive dysfunction, and neuronal death. Methods We aimed to develop novel therapeutic D-amino acid peptides as Tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…ISAD1 and ISAD1rev were tested in cell culture, where it was evident that the peptides were taken up by neuronal Tau expressing cells and accumulated in the cytosol. The peptides were non-toxic to cells and prevented Tau fibril-mediated cell toxicity of externally added and internally expressed Tau (Aillaud et al 2022).…”
Section: Peptides Selected By (Mirror Image) Phage Display or Othermentioning
confidence: 99%
See 1 more Smart Citation
“…ISAD1 and ISAD1rev were tested in cell culture, where it was evident that the peptides were taken up by neuronal Tau expressing cells and accumulated in the cytosol. The peptides were non-toxic to cells and prevented Tau fibril-mediated cell toxicity of externally added and internally expressed Tau (Aillaud et al 2022).…”
Section: Peptides Selected By (Mirror Image) Phage Display or Othermentioning
confidence: 99%
“…Peptide drugs might also have disadvantages such as biological instability and membrane and blood-brain barrier impermeability (Henninot et al 2018), but at least some peptides were demonstrated to cross cell membranes or/and the blood-brain barrier (Pappenheimer et al 1997;Funke et al 2010;Dammers et al 2016;Zhang et al 2020;Malhis et al 2021;Aillaud et al 2022). The problem of in vivo instability due to proteases can be overcome by chemical modification or the usage of D-amino acid peptides (Liu et al 2010;Leithold et al 2016;Lee et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several D-peptides have recently emerged as potential therapeutic candidates for Alzheimer’s disease and other neurological conditions [ 397 , 398 ]. D-peptides, synthetized in D-enantiomer form by mirror image phage display methodology, are designed to extend the half-life of the peptides and increase resistance to enzyme degradation, prolonging in vivo activity [ 399 ].…”
Section: Other Modulators Of the Glycine B Site At Nmdarmentioning
confidence: 99%
“…In particular, D-enantiomeric forms of L-peptides interact with the target proteins of the natural L-amino acid configuration. This technique was employed to develop Tau aggregation inhibitors [ 398 , 400 ] as well as promising D-Aβ-peptides to reduce plaque formation and inflammatory reactions [ 401 , 402 , 403 ] in Alzheimer’s disease.…”
Section: Other Modulators Of the Glycine B Site At Nmdarmentioning
confidence: 99%
“…One such peptide is KLVFF which has been shown to have inhibitory properties on Aβ aggregation, and has been strategically manipulated in order to disrupt pathogenic peptide aggregation [ 22 ]. More recently, Aillaud et al found the novel D-amino acid peptide, ISAD1, successfully inhibited the fibrillization of tau protein [ 23 ]. In addition, studies have also demonstrated a high level of expression of ion channels in microglia implicated in AD that are potentially targetable by synthetic peptide therapy [ 24 ].…”
Section: Introductionmentioning
confidence: 99%